Pengaruh Motivasi Kerja dan Komitmen Kerja Terhadap Produktivitas Kerja ASN dengan Organizational Citizenship Behavior (OCB) Sebagai Variabel Intervening Pada Sekretariat Daerah Kabupaten Pasaman Barat - Angye Mareta Y; Syamsir Syamsir (Journal of Education on Social Science (JESS), 2025)
The productivity of Civil Servants is a crucial factor in supporting the effectiveness of government administration. However, the productivity of ASN at the Regional Secretariat of West Pasaman Regency has not been considered optimal, possibly due to work motivation, work commitment, and Organizational Citizenship Behavior. This study aims to examine the influence of work motivation and work commitment on ASN productivity, with OCB serving as an intervening variable. The research employs an associative quantitative approach to analyze the relationships among these variables. The population includes all 181 ASN at the Regional Secretariat, with a sample of 125 respondents selected using the Slovin formula and proportional random sampling. Data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics and path analysis via SPSS, after performing validity and reliability tests as well as classical assumption tests such as normality, heteroscedasticity, multicollinearity, and linearity. The findings indicate that work motivation and work commitment positively and significantly affect ASN productivity, both directly and indirectly through OCB. Moreover, OCB strengthens the impact of work motivation and commitment on ASN productivity, confirming its role as an effective intervening variable.